1976
DOI: 10.1021/ja00440a030
|View full text |Cite
|
Sign up to set email alerts
|

Boroacetylation of carbohydrates. Correlations between structure and mass spectral behavior in monoacetylhexose cyclic boronic esters

Abstract: The interaction of an acetyl moiety with boron accompanied by the loss of alkyl radical is shown to occur following electron beam ionization in the mass spectrometer. This is similar to the interaction of phosphate with boron previously shown to occur in alkaneboronic esters of certain sugar phosphate dimethyl esters. I n the case of acetates, the interacting moiety can frequently be introduced into a hexose in an equilibrium reaction in which treatment with an alkaneboronic acid is followed by acetylation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(37 citation statements)
references
References 7 publications
0
37
0
Order By: Relevance
“…The reasons for these apparently con¯icting results may relate to the amount and composition of the substrates administered and to the timing of the measurements. Thus in one study the incorporation of 14 C from a 14 C-alanine load into hepatic glycogen was found to be higher in obese Zucker rats in both the fed and 24 h fasted state, 2 whereas in another the incorporation of 14 C-alanine into hepatic glycogen was lower in obese rats 3 ± 4 h after a meal while the incorporation of 14 C-glycerol and 3 H-glucose into hepatic glycogen was similar between obese and lean rats. 1 Hence it is necessary to make simultaneous measurements of glycogen and lipid synthesis in response to a ®xed test meal in order to determine whether the partitioning of substrates between these two processes is different from normal in obese Zucker rats.…”
Section: Introductionmentioning
confidence: 89%
“…The reasons for these apparently con¯icting results may relate to the amount and composition of the substrates administered and to the timing of the measurements. Thus in one study the incorporation of 14 C from a 14 C-alanine load into hepatic glycogen was found to be higher in obese Zucker rats in both the fed and 24 h fasted state, 2 whereas in another the incorporation of 14 C-alanine into hepatic glycogen was lower in obese rats 3 ± 4 h after a meal while the incorporation of 14 C-glycerol and 3 H-glucose into hepatic glycogen was similar between obese and lean rats. 1 Hence it is necessary to make simultaneous measurements of glycogen and lipid synthesis in response to a ®xed test meal in order to determine whether the partitioning of substrates between these two processes is different from normal in obese Zucker rats.…”
Section: Introductionmentioning
confidence: 89%
“…The lactate was removed from the resin using formic acid (0.5 N), which was then evaporated to dryness, dissolved in water and scintillation fluid added. The radioactivity was determined in a liquid scintillation [17]. The butaneboronyl derivative was analysed on a GC/MS (Agilent Technologies, Palo Alto, CA, USA) using a Zebron 1701 column (Phenomenex, Torrence, CA, USA) and selective ion monitoring at 297 and 303 m/z, and a standard curve of known enrichments.…”
Section: Methodsmentioning
confidence: 99%
“…The 13 C natural abundance that is lost by the incorporation of 13 C labels into the molecule will be the difference between eq 12 and 13. We can subtract this difference between eq 12 and 13 from the observed (M+2)/M to get the corrected (M+2)/M: (14) Equation 14 can be simplified to give the useful form of the (M+2)/M 13 C correction: (15) The 13 C correction for the (M+2)/M isotope can be carried out in our matrix equation by adjusting the a 0 (2) values for each isotopomer containing 13 C labels: (16) The above 13 C correction is carried out on the measured isotopic distribution of the unlabeled isotopomer's M+1 and M+2 abundances using eq 11 and 16, respectively. The unlabeled isotopomer's isotopic distribution with the 13 C correction is used in the A matrix in eq 9:…”
Section: Definitions Of Terms and Key Equations Of The Methodsmentioning
confidence: 99%